UCHL3 promotes hepatocellular carcinoma cell migration by de-ubiquitinating and stabilizing Vimentin - Ma, Qiancheng; Lu, Qiliang; Lei, Xiangxiang; Zhao, Jie; Sun, Wen; Wang, Jun; Zhu, Qing; Huang, Dongsheng (Frontiers in Oncology, 2023)
Background Hepatocellular carcinoma (HCC) is a common malignant tumor associated with a poor prognosis. Ubiquitin carboxyl-terminal hydrolase L3 (UCHL3) has been reported to promote diverse tumors, but little is known about its role in HCC. Methods Expression levels of UCHL3 in Huh7 and Hep3B cells were measured by qRT-PCR. UCHL3, Vimentin protein levels, and ubiquitination levels were determined by Western blot assay. co-immunoprecipitation, Immunofluorescence, and IHC were used to detect the interaction and expression association between UCHL3 and Vimentin in the cells. Wound healing and Transwell assays were used to measure cell migration. Spheroid formation assay were used to assess stem-like properties. Results UCHL3 expression was found to be significantly elevated in HCC and associated with poor prognosis. UCHL3 promoted migration and stem-like properties of HCC cells. Vimentin was identified as a potential de-ubiquitination substrate of UCHL3 and UCHL3 interacted with and promoted the de-ubiquitination of Vimentin, enhancing its stability. Moreover, the suppression of UCHL3 by siRNA or the inhibition by TCID upregulated ubiquitinated Vimentin. Vimentin attenuated the suppression of cell migration caused by knockdown of UCHL3. Conclusion UCHL3 was highly expressed in HCC and functioned as an oncogene. Vimentin is a novel substrate of UCHL3 and its stabilization and de-ubiquitination enhanced HCC cell migration.